Ciprofloxacin Induction of a Susceptibility Determinant in Pseudomonas aeruginosa - Brazas, Michelle D. (American Society for Microbiology, 2005)
With few novel antimicrobials in development, resistance to the current selection of antibiotics increasingly encroaches on our ability to control microbial infections. One limitation in our understanding of the basis of the constraints on current therapies is our poor understanding of antibiotic interactions with bacteria on a global scale. Custom DNA microarrays were used to characterize the response of Pseudomonas aeruginosa to ciprofloxacin, a fluoroquinolone commonly used in therapy against chronic infections by this intrinsically resistant bacterium. Of the approximately 5,300 open reading frames (ORFs) on the array, 941 genes showed statistically significant (P ≤ 0.05) differential expression in response to 0.3× MIC of ciprofloxacin; 554 were promoted and 387 were repressed. Most striking among the responsive genes was the region between PA0613 and PA0648, which codes for the bacteriophage-like R2/F2 pyocins. In this region, virtually every ORF was increased by 0.3× MIC of ciprofloxacin and even more dramatically up-regulated (7- to 19-fold) following treatment with 1× MIC of ciprofloxacin. Pyocin gene expression was confirmed with lux reporter mutants and real-time PCR studies; pyocin-like particles were also present in transmission electron micrographs of supernatants from cells treated with 1× MIC of ciprofloxacin. Interestingly, mutants in this region exhibited ≥8-fold-increased resistance to ciprofloxacin and other fluoroquinolones, demonstrating that this region is a susceptibility determinant. Since this region is known to be variably present in the genomes of clinical isolates of P. aeruginosa (R. K. Ernst et al., Environ. Microbiol. 5:1341-1349, 2003, and M. C. Wolfgang et al., Proc. Natl. Acad. Sci. USA 100:8484-8489, 2003), these findings demonstrate that the R2/F2 pyocin region is a “loaded gun” that can mediate fluoroquinolone susceptibility in P. aeruginosa.